Performance factors in the new combined event of modern pentathlon - Le Meur, Y.; Hausswirth, C.; Abbiss, C.; Baup, Y.; Dorel, S. (Journal of Sports Sciences, 2010)
The aims of this study were to determine (1) the individual tactics employed by elite modern pentathletes within each discipline of the new combined running-shooting event, and (2) the consequences of these strategies on overall performance. For 36 male pentathletes competing in a World Cup event, we measured running velocity, transition time, shooting time, shooting accuracy, and delay per shot. Performances of the top third of athletes, middle third of athletes, and the bottom third of athletes in the combined event were compared. The difference in overall performance between the top third and middle/bottom thirds was predominately associated with better shooting accuracy (79 ± 13%, 68 ± 12%, and 64 ± 10% success rate for top, middle, and bottom third, respectively) and faster shooting time (86 ± 16 s, 109 ± 19 s, and 117 ± 23 s for top, middle, and bottom third, respectively). No significant differences in running velocity, transition time or delay per shot were observed among the three groups. All the competitors started significantly faster over the first 200 m of each of the three 1-km running stages. The last third of the approximately 3-km race was completed significantly faster by all athletes (P < 0.05). The main finding was that the best performers of the combined event distinguished themselves due to their greater shooting accuracy.